(untitled) (REDEL. Revista Granmense de Desarrollo Local, 2023)
The formation of the human being constitutes a constant of the pedagogical formation in Fidel Castro’s thought, which requires permanent study to understand the revolutionary behavior of the people. It helps to understand the organic synthesis of his political performance in order to build the bases to face the complex problems of the relationship between neo-colony and social transformation, focusing on the political process. The article is framed in the homage to the historical leader of the Cuban Revolution on the occasion of the seventieth anniversary of the assault to the Moncada and Carlos Manuel de Céspedes barracks. The objective is to reflect on the construction of the political pedagogy with which Fidel thought about the revolutionary formation of the human being before, during and after January 1959. The commitment that such an assessment represents demands from revolutionaries, to strengthen its relevance, the effectiveness and efficiency of the improvement processes, its responsibility and inclusive practices in favor of social transformation in all its dimensions, mainly in the economic, socio-cultural and environmental fields. At the same time, education is endorsed as a public and social good, a universal human right, and a duty of the Cuban Revolution. The methodology used revolved around the method of analysis and critique of documentary sources and their theoretical synthesis, accompanied by the dialectical-materialist and historical-logical method.